142 All employees resilient through aggression aftercare': the development of a digital platform supporting aggression aftercare in health care teams. (24th April 2018) - Delvaux, E; Leirs, H; Schrijvers, J; Konovaloff, I; Godderis, L
Abstract : Introduction: Health care workers are often confronted with aggression, impairing their well-being at work. Aggression aftercare, adjusted to the personal needs of victims, may facilitate their recovery, return to and well-being at work. Methods: We used three methodologies to identify the most important needs for employees confronted with workplace aggression. First, fictive aggression incidents were reenacted in four organisations. After each scene, actors and audience discussed about impact and needs after encountering such incidents. Second, aggression experts (n=10) were interviewed about existing and ideal aggression procedures within their institutions. Third, a diary questionnaire (of two weeks) was administered to employees (n=11) that recently encountered workplace aggression. Results: Bringing together the input from the different methodologies by defining common and frequently re-occurring themes, we identified the most central needs of aggression victims: the need for acknowledgement, the need for support by colleagues and supervisor and the need for openness about aggression. Based on these needs, we conceptualised a program to facilitate aggression aftercare in teams. More specifically, on a digital platform, aggression victims can report that they encountered aggression, what impact this has on them and which colleague should contact them to talk about it. After saving the incident on the platform, an e-mail cascade will be set in motion to notify different actors about their responsibilities in the process of providing aftercare. The 'aftercare'-colleague will be most central to the aftercare process, supporting the victim both emotionally and practically. Depending on the rated impact, the supervisor will also play a central role in the aftercare process. Conclusion: Because aggression victims can personalise their incident report (by choosing the incident's impact and their preferred 'aftercare'-colleague), the aftercare will be more adjusted to their needs, which may increase resilience after aggression. The program effectiveness will be tested within a health care setting.